TAX INCENTIVES THAT ENABLE FOREIGN DIRECT INVESTMENT - Swart, Izak Wessels (My University, 2011)
South Africa as developing nation does not attract foreign direct investment in the same quantities as other developing nations. The project examines what foreign direct investment constitutes, the benefits associated with foreign direct investment for host countries and trends in foreign direct investment. Tax incentives associated with foreign direct investment are examined to establish what tax incentives South Africa can offer international investors to enable more foreign direct investment into South Africa. The work is based on a literature review. The findings are that certain matters in South Africa reduce South Africa‟s chances of obtaining foreign direct investment. Tax incentives should be offered to offset these matters
MBA thesis - WBS
Keywords: Taxation - incentives; Foreign direct investment